THE INFLUENCE OF QUALITY SERVICE FOR CUSTOMER SATISFACTION : CASE STUDY IN ZADJ PROSALON BALIKPAPAN - Hermawansyah, Adi; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (Nusantara Economics and Entrepreneurships Journals, 2024)
The objective of this research to determine the effect of Service Quality on customer satisfaction at Zadj Prosalon Balikpapan which is motivated by the phenomenon of more and more people who care about their appearance, namely beauty care and the emergence of various Beauty Salon Businesses in the Balikpapan community, therefore companies need to retain customers not only with good product quality but also through service quality that needs to be continuously monitored and improved in order to achieve optimal customer satisfaction because customer quality and satisfaction hold crucial stakes for success and survival in today's market competition. Customer quality and satisfaction are closely related to market share and customer retention. Increased customer retention implies greater positive word-of-mouth information distribution, reducing price sensitivity which ultimately results in better business performance. This study was conducted on customers who came and had treatments more than 2 times. The sampling technique was nonprobability sampling. The analysis method used in this study is multiple linear regression analysis and questionnaires as a means of collecting respondent data are then processed with the help of the SPSS Statistics program with a sample size of 295. Data analysis techniques used in this study are validity test, reliability test, multicollinearity test, heteroscedasticity, autocorrelation, F-test, t-test. Based on the results obtained from this study, service quality has a positive and significant effect on Customer Satisfaction at Zadj Prosalon Balikpapan. Quality has an effect of 75.2% on customer satisfaction, while the remaining 24.8% is influenced by service variables, other variables not examined in this study